Development of Sparkol VideoScribe Audiovisual Learning Media with Problem-Based Learning Model for Arabic Vocabulary Mastery - Diana Fitri Islami; Abdul Hafidz bin Zaid; Muhammad Ismail (Arabiyatuna: Jurnal Bahasa Arab, 2026)
Mastering Arabic vocabulary is crucial for supporting students' language proficiency, especially in Islamic boarding schools where Arabic serves both religious and daily communication purposes. However, vocabulary acquisition remains challenging due to conventional methods that rely on rote memorization and lack engaging media. While previous studies have explored audiovisual-based PBL separately, few have integrated both specifically for Arabic vocabulary in pesantren contexts. This study aims to develop an effective audiovisual-based PBL to enhance vocabulary mastery. Employing Research and Development (R&D) with the 4D model (Define, Design, Develop, Disseminate), this research included needs analysis, media design, expert validation, and effectiveness testing through pre-test and post-test. Data analysis involved normality tests, homogeneity tests, and paired sample t-tests to measure effectiveness. Results show that the developed media is valid and feasible according to experts and significantly improves students’ vocabulary mastery, with a mean difference = -28.729, t = -17.170, and Sig. (2-tailed) = 0.000 < 0.05, indicating a significant difference between pre-test and post-test scores. This research demonstrates that the application of audiovisual media in conjunction with PBL can produce more meaningful learning, improve retention, and enhance students' critical thinking skills. These findings provide practical contributions in the form of new strategic options for Arabic language teachers and reinforce the urgency of implementing audiovisual-based PBL in modern education.